Using Animated Short Story for Joyful and Effective Classroom Writing at the Second Grade Students of SMA Ulul Albab Makassar - Sri Hariati Mustari; Nurhusnil Khatimah; Muhammad Ilham Ali (Journal of English Language Teaching, Literature and Culture, 2023)
The research was aimed at finding out whether or not using animated short story was effective to improve the students achievement to create students joyfulness in writing classroom and whether or not students joyfulness have a correlation with students writing achievement The research was carried out under the quantitative paradigm with quasi experimental design Class VIII 1 and Class VIII 2 were chosen as the samples of this research obtained through cluster sampling technique from the population that consisted of 56 students The data of the students writing ability were collected by using writing test and questionnaire The data collected were then analyzed through descriptive and inferential statistics through SPSS 20 0 program The research result showed that using animated short story was more effective than unanimated story in improving the students writing achievement It s seen from the significance t test result that reveals the significance value is lower than the significance < p>